Selenomethionine alleviates T-2 toxin-induced articular chondrocyte ferroptosis via the system Xc−/GSH/GPX4 axis - Fang-fang Yu; Juan Zuo; Miao Wang; Shui-yuan Yu; Kang-ting Luo; Tong-tong Sha; Qian Li; Zai-chao Dong; Guo-yu Zhou; Feng Zhang; Xiong Guo; Yue Ba; et al. (Ecotoxicology and Environmental Safety)
T-2 toxin can induce bone and cartilage development disorder, and oxidative stress plays an important role in it. It is well known that selenomethionine (Se-Met) has antioxidative stress properties and promotes the repair of cartilage lesion, but it remains unclear whether Se-Met can relieve damaged cartilage exposure to T-2 toxin. Here, the oxidative stress and ferroptosis of chondrocytes exposure to T-2 toxin were observed. Mechanistically, T-2 toxin increased ROS, lipid ROS, MDA and Fe2+ contents in chondrocytes, decreased GSH and GPX4 activity, and inhibited the system Xc−/GSH/GPX4 antioxidant axis. In addition, the mitochondria of chondrocytes shrunk and the mitochondrial crest decreased or disappeared. However, Fer-1 (Ferrostatin-1) inhibited ferroptosis induced by T-2 toxin in chondrocytes. The Se-Met alleviated lipid peroxidation, oxidative stress, and damaged mitochondrial in T-2 toxin-infected chondrocytes, enhanced antioxidant enzyme activity, and activated the system Xc−/GSH/GPX4 axis, thereby antagonizing ferroptosis of chondrocytes and alleviating articular cartilage damage. In conclusion, our findings highlight the essentiality of ferroptosis in chondrocyte caused by T-2 toxin, elucidate how Se-Met offers protection against this injury and provide research evidence for the drug treatment target of Kashin-Beck disease.